CURAHAN TENAGA KERJA PADA USAHATANI PADI ORGANIK DI PROVINSI LAMPUNG - Sri Puji Lestari; Sri Handayani; Yuni Elmita Sari; Yeyen Ilmia Sari; Aji Setiya Bakti; Nyang Vania Ayuningtyas Harini (AgriMalS, 2022)
One form of sustainable farming system is organic farming. Indonesian people are starting to realize the importance of a healthy lifestyle that starts with healthy food, making the need and demand for organic agriculture increase. Organic rice is rice produced through rice cultivation without the use of chemical fertilizers and pesticides. Lampung Province is a province that has the potential to produce organic rice. The purpose of the study was to examine the labor outpouring of organic rice farmers in Lampung Province. The study was located in Beringin Kencana Village, Candipuro District, South Lampung Regency and Purwokencono Village, Sekampung Udik District, East Lampung Regency in July-August 2022. Sampling was carried out using the census method. The analytical method used is descriptive analysis. The results showed that the average labor force for organic rice farming was 184.11 HKP/Ha. The highest labor outpouring was in harvesting activities, which was 43.99 HKP/Ha or 24%. Then followed by planting activities as much as 21.36 HKP/Ha or 12%, and followed by land management activities as much as 18.66 HKP/Ha or 10%.